A CASE STUDY OF FACTORS CONTRIBUTING TO SUCCESSFUL SECOND LANGUAGE ACQUISITION - Terri Chen (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Every case of second language learning is different, but they are often influenced by systematic factors. What causes a learner to succeed or fail? In this case study, the language learning experiences of a single nonnative English speaker who successfully acquired English sheds light on the interplay between several of these aspects. An interview with a single adult subject reveals that for this particular individual, a high aptitude, as well as identity and personality characteristics that aligned with an openness to experience and learning in general, were more effective than factors of motivation. While identifying how and why a single individual may be successful or unsuccessful might not be generalizable to all learners, it can serve as a tool in helping to understand differences in L2 learning success.